Change in gait speed and adverse outcomes in patients with idiopathic pulmonary fibrosis: a prospective cohort study - Nolan,CM; Schofield,SJ; Maddocks,M; Patel,S; Barker,RE; Walsh,JA; Polgar,O; George,PM; Molyneaux,PL; Maher,TM; Cullinan,P; Man,WD-C (Respirology, 2023)
BACKGROUND AND OBJECTIVE: Gait speed is associated with survival in individuals with idiopathic pulmonary fibrosis (IPF). The extent to which four-metre gait speed (4MGS) decline predicts adverse outcome in IPF remains unclear. We aimed to examine longitudinal 4MGS change and identify a cut-point associated with adverse outcome. METHODS: In a prospective cohort study, we recruited 132 individuals newly diagnosed with IPF and measured 4MGS change over 6 months. Death/first hospitalization at 6 months were composite outcome events. Complete data (paired 4MGS plus index event) were available in 85 participants; missing 4MGS data were addressed using multiple imputation. Receiver-Operating Curve plots identified a 4MGS change cut-point. Cox proportional-hazard regression assessed the relationship between 4MGS change and time to event. RESULTS: 4MGS declined over 6 months (mean [95% CI] change: -0.05 [-0.09 to -0.01] m/s; p = 0.02). A decline of 0.07 m/s or more in 4MGS over 6 months had better discrimination for the index event than change in 6-minute walk distance, forced vital capacity, Composite Physiologic Index or Gender Age Physiology index. Kaplan-Meier curves demonstrated a significant difference in time to event between 4MGS groups (substantial decline: >-0.07 m/s versus minor decline/improvers: ≤-0.07 m/s; p = 0.007). Those with substantial decline had an increased risk of hospitalization/death (adjusted hazard ratio [95% CI] 4.61 [1.23-15.83]). Similar results were observed in multiple imputation analysis. CONCLUSION: In newly diagnosed IPF, a substantial 4MGS decline over 6 months is associated with shorter time to hospitalization/death at 6 months. 4MGS change has potential as a surrogate endpoint for interventions aimed at modifying hospitalization/death.